PENGARUH PENGETAHUAN PEMILIK, MANFAAT YANG DIRASAKAN, DUKUNGAN PEMERINTAH, DAN DORONGAN EKSTERNAL TERHADAP PENGADOPSIAN E-COMMERCEBERBASIS MEDIA SOSIAL - Febrina Mahliza (Jurnal Ilmiah Manajemen dan Bisnis, 2018)
Many of MSME’s especially micro enterprises are still not utilizing social media as a media of product promotion. This study aims to determine the adoption of e-commerce based on social media on micro business, which is about the factors that affect the adoption. The research was conducted on 100 respondents of micro business actors in Jabodetabek taken by purposive sampling method. Data were analyzed using structural equation modeling with Partial Least Square (PLS) approach. The results show that the adoption of social media-based e-commerce conducted by micro enterprises is influenced by knowledge of the owner, perceived benefits and external drives. The government support factor has no significant effect on the adoption of e-commerce because there is no government support in a concrete policy for micro enterprises.